Aktualisasi Peran Mahasiswa STIBA Makassar melalui Program KKN di Desa Mamampang, Kabupaten Gowa, Sulawesi Selatan - Syandri Syandri (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
Mamampang is one of the areas in Gowa Regency, South Sulawesi, which geographically means an area that is quite far from urban areas. With these conditions, this area really needs assistance in community development, especially religious development. To help solve this problem, STIBa Makassar held Real Work Lecture (KKN) activities at this place as part of actualizing the role of STIBA students by compiling coaching programs for village communities which is also part of one of the pillars of the Tri Dharma of Higher Education. The method of implementing the community service program begins with mapping community problems and needs using SOAR analysis. After the analysis was carried out, the main program was prepared in the form of teaching TK/TPA, Dirosah Teaching, Implementation of preacher training, Friday preaching and also carrying out teaching programs in schools or Islamic boarding schools. All of these programs have been running well and have shown initial results in accordance with the stated KKN objectives.